Efektivitas Pelayanan Program Home Care Saat Masa Pandemi Covid19 di Puskesmas Jumpandang Baru Kota Makassar - Aliyah Maulidyana; Suci Rahmadani; Balqis Balqis (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Effectiveness states that the patient’s right is to get health services in accordance with services in accordance with service standards. Some of the programs provided can be in the form of public health insurance, free health up to health services that directly touch the community through the home care program. During the pandemic, people reduced activities outside the home. The home care program is expected to able be serve people’s complaints who want to get health services even at home. Study is aims determine to the effectiveness of home care program during services the pandemic at the Jumpandang Baru Health Center in Makassar City. This type of research uses a quantitative research design with descriptive methods. This study in population all people who used home care services pandemic during the covid-19 in 2020-2021 residing in the Jumpandang Baru health center area. This study sample used a total sampling of 70 respondents. The results of the study show that on average., the home care service program during the covid-19 pandemic was very effective. Judging from the five variable sizes, namely program understanding, on time, goal achievement, ,right on target and real change. Several respondents also stated that the home care service program during the pandemic provided many benefits. The conclusion study is that all the variables examined in this study show the effectiveness of the home care service pandemic at the Jumpandang Baru health center program during the covid-19, it is hoped that the Jumpandang Baru health center can continue to improve health services even though only at home.